Disentangling the coupling relationships between functional denitrifiers and nitrogen transformation during cattle-manure and biochar composting: A novel perspective. (January 2023) - Deng, Liting; Liu, Wanying; Chang, Nuo; Sun, Lei; Zhang, Jizhou; Bello, Ayodeji; Uzoamaka Egbeagu, Ugochi; Shi, Shuai; Sun, Yu; Xu, Xiuhong
Graphical abstract: Highlights: Biochar altered the transformation relationships from ONCs to NH4 + -N. Biochar up-regulated nir gene transcription but inhibited NIR activity. Denitrifying bacteria could participate in the process of ONCs transformation. Denitrification is dominated by nirK -denitrifiers rather than nirS -denitrifiers. Biochar altered single and combined nir -denitrifier co-occurrence patterns. Abstract: This study explored the coupling relationships between denitrifiers and N -transformation using multi-level (DNA, RNA and enzyme) and multi-aspect (abundance, diversity, structure, key community, network pattern, and functional module) analyses during cattle-manure (CM) and biochar (CMB) composting. Amino sugar-N (ASN, 0.914) and hydrolysable unknown-N (-0.724) were main organic-N components mediating NH4 + -N in CM and CMB, respectively. Biochar lowered nirK, nirS, and nosZ genes copies, up-regulated nir gene transcripts, and inhibited nitrite reductase (NIR) activity. For nirK -denitrifiers, Luteimonas was predominant taxa influencing NO2 − -N and amino acid-N (AAN). Unclassified_k_norank_d_Bacteria and unclassified_p_Proteobacteria regulated NO3 − -N and ASN, respectively. These three genera played crucial roles in mediating NIR activity and nosZ/nirK. For nirS -denitrifiers, Paracoccus and Pseudomonas mediated NH4 + -N and AAN, respectively, and they were vital genera regulating NO3 − -N, ASN and NIR activity. Furthermore, nirK -denitrifiers was major contributor to denitrification. Overall, functional denitrifiers might simultaneously participate in multiple N -transformation processes.